Clevudine in people with chronic hepatitis B virus infection - Ricaforte‐Campos, Jane D (Cochrane Database Syst Rev, 2016)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the benefits and harms of clevudine versus placebo, no intervention, or any of the nucleoside/nucleotide analogues, in people with chronic HBV infection.